Application of Prigogine-Flory-Patterson-Theory to Excess Molar Volumes of Difuryl methane + (C1-C6)alkan-1-ol Binary Mixtures at 298.15 K and Atmospheric Pressure - Ddamba, W.A.A.; Mokoena, T.T. (Asian Journal of Chemistry, 2014)
The recently reported excess molar volume (VmE) data for difuryl methane + (C1-C6) alkan-1-ol binary mixtures as a function of composition at T = 298.15 K under atmospheric pressure have been used to test the applicability of Prigogine-Flory-Patterson theory. An analysis of each of the three contributions viz., interactional volume (VEint), free volume (VEfv) and characteristic pressure (VEP*) to VmE show that the VEfv contribution was small and as expected negative for all difuryl methane + (C1-C6) alkan-1-ol binary mixtures, exhibiting a decrease with the alka-1-ol chain length. The VEP* contribution was large and negative for mixtures containing methanol, ethanol and propan-1-ol and determined the overall experimental shape of VmE isotherms for difuryl methane + (C1-C3) alkan-1-ol binary mixtures. For difuryl methane + (C4-C6) alkan-1-ol binary mixtures, large and positive magnitudes of VEP* and VEint contributions are the most important in accounting for the experimental shapes of VmE isotherms. The correlation between the theoretical excess molar volumes (VEPFP) and experimental VmE data was satisfactory for difuryl methane + (methanol or ethanol or hexan-1-ol) binary mixtures and inadequate for difuryl methane + (propan-1-ol, or butan-1-ol, or pentan-1-ol) binary systems.